No One Wants to Hire Us: The intersectional precarity experienced by Venezuelan LGBTQ+ asylum seekers in Brazil during COVID-19 - Su, Yvonne (Anti-Trafficking Review, 2023)
This article presents a case study of how COVID-19 has increased the precarity and risks of labour exploitation for vulnerable populations. Looking at the situation of LGBTQ+ Venezuelan asylum seekers in Brazil during COVID-19, it examines how the challenges they faced were exacerbated during the pandemic and how the Brazilian government’s poor response to COVID-19 and lockdown policies forced LGBTQ+ Venezuelan asylum seekers to take greater risks that exposed them to the virus. Based on 56 surveys with LGBTQ+ Venezuelan asylum seekers in Manaus, Brazil, the article discusses how COVID-19 impacted the livelihoods of LGBTQ+ Venezuelan asylum seekers. Specifically, it demonstrates that transgender and travesti Venezuelan asylum seekers experienced more labour precarity, discrimination, and violence during the pandemic than their cisgender counterparts.